Building information modelling and project information management framework for construction projects - Olawumi, Timothy O.; Chan, Daniel W. M. (Journal of Civil Engineering and Management, 2019)
The study aims to develop an effective BIM-project information management framework (BIM-PIMF) and associated assessment model for construction projects with a view to enhancing the functional management of project information. An explanatory case study technique and case study evidence from four BIM construction projects form the study’s research design. The study identified and established the three sub-criteria of the BIM-PIMF model which are the BIM process level factors, BIM product level factors, and the key indicators for a successful BIM deployment on construction project sites. These criterias were semantically linked to the development of the BIM-PIMF framework on a five-point metric scale. The deliverables of this study include the development of the BIM-PIMF framework, together with its analytical scoring system. The findings of the study will improve the information channels of and ease the integration of technological innovations in construction processes while improving the technical competencies of project staff. The study highlighted a basket of effective recommendations and strategies to enhance the deployment of BIM throughout a project lifecycle. Policymakers and government departments can utilize the model in assessing the level of usage of BIM in a construction project as one of the useful measures in gauging which construction firms to be provided subsidies.